2008
DOI: 10.1016/j.cgh.2007.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Racial and Ethnic Disparities in the Prevalence of Barrett’s Esophagus Among Patients Who Undergo Upper Endoscopy

Abstract: Background & Aims-The incidence of esophageal adenocarcinoma (EAC) in blacks and Hispanics is well-described, but racial differences in the risk of Barrett's esophagus (BE) have not been directly studied. It is important to determine whether race and ethnicity can be identified as risk factors for the development of metaplasia, neoplastic progression, or both.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
100
3
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 113 publications
(108 citation statements)
references
References 20 publications
3
100
3
2
Order By: Relevance
“…The incidence of Barrett's oesophagus, meanwhile, seems to have been stable in the United States (Cameron et al, 1990;Macdonald et al, 1997;Conio et al, 2001;Corley et al, 2009), which is in marked contrast to ADC (Figure 1). It has been reported that the proportion presenting with reflux as an indication for endoscopy is highest in Whites, followed by Hispanics and then Blacks (Abrams et al, 2008), which is parallel to the incidence order of Barrett's oesophagus and ADC. In addition, evidence suggests that although Whites, Blacks, and Asians report a similar prevalence of heartburn, Whites are more likely to suffer from erosive reflux disease (Spechler et al, 2002;El-Serag et al, 2004;Corley et al, 2007).…”
Section: Discussionmentioning
confidence: 81%
“…The incidence of Barrett's oesophagus, meanwhile, seems to have been stable in the United States (Cameron et al, 1990;Macdonald et al, 1997;Conio et al, 2001;Corley et al, 2009), which is in marked contrast to ADC (Figure 1). It has been reported that the proportion presenting with reflux as an indication for endoscopy is highest in Whites, followed by Hispanics and then Blacks (Abrams et al, 2008), which is parallel to the incidence order of Barrett's oesophagus and ADC. In addition, evidence suggests that although Whites, Blacks, and Asians report a similar prevalence of heartburn, Whites are more likely to suffer from erosive reflux disease (Spechler et al, 2002;El-Serag et al, 2004;Corley et al, 2007).…”
Section: Discussionmentioning
confidence: 81%
“…Although the evidence for lower prevalence of BE in African Americans compared with Caucasians is consistent ( 48,49 ), the results of studies comparing BE incidence in Hispanics and nonHispanic whites are inconsistent, likely refl ecting the heterogeneity of the Hispanic population ( 49,50 ).…”
Section: Summary Of Evidencementioning
confidence: 99%
“…Understanding the interactions in the BE pathogenesis between H. pylori, host, racial disparity and environmental factors may be absolutely difficult, because synergistic effects among these factors including H. pylori virulence need to be taken into account. [60][61][62] Further studies on the genetic and epigenetic alterations of H. pylori-related BE are awaited in not only Asian populations with a high rate of H. pylori infection but also in Western countries.…”
Section: Discussionmentioning
confidence: 99%